Several Open Questions Regarding the Right to Severance Pay in the Republic of Serbia - Balšić, Anja (Glasnik Advokatske komore Vojvodine, 2025)
The aim of this paper is to explain the nature of right on severance pay of employees in situation when employer resorts to collective redundancies due to economic, organizational or technological changes. The questions which are open concern the validity of the establishment of public funds that would participate together with the employer in the payment of severance pay and their financing, as well as the suitability of foreign investors to use money from public funds during the collective dismissal of employees. In addition, the author observes the existence of a problem related to the autonomy of employers to make business decisions regarding economic, organizational and technological changes and the (un)justified intrusion of courts into such decisions. The paper also gives a recommendation about the moment that is considered relevant, whether certain persons are connected, and in terms of realizing the right to severance pay for employees. Certain solutions of the domestic legislator were criticized, and potential future solutions were proposed. The right of employees to severance pay is first of all viewed from the perspective of domestic positive law, but with regard to certain related institutes, comparative law solutions were also mentioned. Author as well provides brief review of the overview of other measures that the employer can take before the termination of the employment contract on the aforementioned basis and the payment of severance pay. Keywords: severance pay, collective dismissal, redundancy, public funds, employment measures.